AI and Children: Challenges and Protection Strategies - Imelda Martinelli; Tesalonika Valerie Limmartin; Priscilla Angelia Daya; Alberta Alva Debora Kambun; Meilody Patricia (Jurnal Ragam Pengabdian, 2026)
The development of artificial intelligence (AI) has brought about major changes in the field of law, including child protection in the context of civil and matrimonial law. The use of AI has the potential to improve the effectiveness of protection through early detection and more accurate data management. However, its application also poses new challenges related to privacy, ethics, and inadequate legal regulations. The purpose of this study is to analyze the implications of AI implementation in child legal protection, particularly in the context of civil and matrimonial law, and to identify various challenges that arise in its implementation. This study uses a normative legal research method. Two types of legal materials are used in this study, namely primary legal materials and secondary legal materials. The data collection techniques used in this study are library research and online research of various relevant legal sources. The data obtained is then analyzed using qualitative descriptive analysis. The results of the study show that the application of AI has implications for the legal protection of children in civil and marriage law. AI helps with the early detection of child marriage and violence, but raises issues of legal responsibility, privacy violations, and regulatory gaps. Legal reforms, increased digital literacy, and the application of child- centered AI principles are needed to strengthen child protection in the digital age.